2021
DOI: 10.3344/kjp.2021.34.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral current-source distribution associated with pain improvement by non-invasive painless signaling therapy in patients with failed back surgery syndrome

Abstract: Background Non-invasive painless signaling therapy (NPST) is an electro-cutaneous treatment that converts endogenous pain information into synthetic non-pain information. This study explored whether pain improvement by NPST in failed back surgery syndrome (FBSS) patients is related to cerebral modulation. Methods Electroencephalography (EEG) analysis was performed in 11 patients with FBSS. Subjects received daily NPST for 5 days. Before the first treatment, patients com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…The peripheral stimulus-derived opioids 5-hydroxytryptamine (5-HT) and norepinephrine in the CNS are believed to regulate inflammatory and neuropathic pain ( 30 , 31 ). A study using electroencephalography suggested that pain improvement following electrocutaneous treatment in patients with FBSS was associated with increased cerebral activity, primarily in the anterior cingulate gyrus, which participates in pain and emotion processing ( 32 , 33 ). Likewise, the acupoint LR3 employed in this case is recognized for its modulatory effects on pain perception and emotional functions ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral stimulus-derived opioids 5-hydroxytryptamine (5-HT) and norepinephrine in the CNS are believed to regulate inflammatory and neuropathic pain ( 30 , 31 ). A study using electroencephalography suggested that pain improvement following electrocutaneous treatment in patients with FBSS was associated with increased cerebral activity, primarily in the anterior cingulate gyrus, which participates in pain and emotion processing ( 32 , 33 ). Likewise, the acupoint LR3 employed in this case is recognized for its modulatory effects on pain perception and emotional functions ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…FBSS remains difficult to manage due to its lack of precise pathophysiology and complexity of causes, and various clinical symptoms ( 18 ). In FBSS management, level one treatment includes pharmacological and non-pharmacological therapy, such as acupuncture and physiotherapy ( 18 , 19 ). Level two treatment is recommended when level one treatment is unsuccessful; it includes selective root block, other spinal injections, and epidural adhesiolysis ( 18 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors recommended the application of IDD for CPSS when SCS and DRG stimulation treatment cannot provide satisfying pain relief (Level Ⅱ) [ 121 ]. In addition, a recent study showed that non-invasive painless signaling therapy (NPST) relieved the pain of CPSS patients [ 122 ]. NPST is an electrodermal therapy that converts pain information into synthetic non-pain information [ 122 ].…”
Section: Current Treatment Of Cpssmentioning
confidence: 99%
“…In addition, a recent study showed that non-invasive painless signaling therapy (NPST) relieved the pain of CPSS patients [ 122 ]. NPST is an electrodermal therapy that converts pain information into synthetic non-pain information [ 122 ]. Electroencephalography data suggest that pain reduction by NPST in CPSS patients was associated with increased activity in the right anterior cingulate gyrus.…”
Section: Current Treatment Of Cpssmentioning
confidence: 99%